1989
DOI: 10.1203/00006450-198905000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Placental Glucose Transfer and Consumption by Fetal Glucose Production

Abstract: ABSTRACT. We studied ten normoglycemic [maternal glucose (GA) = 70 mg/dL] and six insulin-induced hypoglycemic (GA = 22 mg/dL) pregnant sheep to test the hypothesis that development of fetal glucose production (GPR) could help maintain fetal glucose concentration, limit uteroplacental-fetal glucose transfer (UPGT), and sustain uteroplacental glucose consumption (UPGC). Compared with the normoglycemic group, the hypoglycemic group demonstrated the following values: fetal glucose concentration (G,) was 9.8 + 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 13 publications
4
35
0
Order By: Relevance
“…Glucose accounts for a higher proportion of oxygen consumption in the foetal foal (about 40% [33]) or foetal pig (35-40% [34]) than in the foetal lamb (about 30% [35][36][37]) during late gestation. In the case of maternal hypoglycaemia induced by fasting, the contribution of exogenous glucose to foetal requirements is reduced to approximately half of the normal value in sheep [30], its foetal utilisation is decreased, and foetal gluconeogenesis is increased [15,38]. It was even shown by Hodgson et al [39] that 44% of the glucose used by twin foetuses from well-fed ewes was provided by foetal gluconeogenesis.…”
Section: Glucosementioning
confidence: 99%
“…Glucose accounts for a higher proportion of oxygen consumption in the foetal foal (about 40% [33]) or foetal pig (35-40% [34]) than in the foetal lamb (about 30% [35][36][37]) during late gestation. In the case of maternal hypoglycaemia induced by fasting, the contribution of exogenous glucose to foetal requirements is reduced to approximately half of the normal value in sheep [30], its foetal utilisation is decreased, and foetal gluconeogenesis is increased [15,38]. It was even shown by Hodgson et al [39] that 44% of the glucose used by twin foetuses from well-fed ewes was provided by foetal gluconeogenesis.…”
Section: Glucosementioning
confidence: 99%
“…Experimental models in pregnant sheep of reduced fetal glucose supply, producing physiological hypoglycemia, include acute hypoglycemia induced by maternal fasting for several days (10,20), prolonged maternal insulin infusions (5,6,17,38,46), or placental insufficiency resulting in IUGR (28,44,45,50). In these studies, increased fetal glucose production rates were identified when fetal glucose utilization rates remained greater than the net rate of glucose uptake from the placenta (19).…”
mentioning
confidence: 91%
“…To induce hypoglycemia, a continuous, variable rate infusion of insulin was initiated into the maternal vein (infusate concentration ϭ 1.7 U/ml, Humulin R; Eli Lilly, Indianapolis, IN) in 0.5% BSA (Sigma, St. Louis, MO; in 0.9% NaCl). Maternal arterial plasma glucose was measured at least twice daily and the maternal insulin infusion was adjusted to produce and maintain a 50% reduction relative to the basal period (2,5,6). Fetal metabolic studies described above were repeated on d1 and d4 of hypoglycemia.…”
Section: Methodsmentioning
confidence: 99%
“…The ewes were housed in a room with the temperature controlled between 10 and 20°C. At least two sheep were always housed together for company (6,7 Maternal arterial blood was sampled daily or twice daily for measurement of glucose and insulin concentration. The maternal arterial whole-blood glucose concentrations were used to adjust the insulin infusion rate to achieve a desired arterial whole-blood glucose concentration of approximately 1.4 mmol/L (25 mg/dL), representing an estimated reduction of 50% from normal.…”
Section: Methodsmentioning
confidence: 99%